On approximation of approximately quadratic mappings by quadratic mappings - Rassias, John Michael (Annales Mathematicae Silesianae, 2001)
In this paper we establish an approximation of approximately quadratic mappings by quadratic mappings, which solves the pertinent Ulam stability problem.